Relations between Islam and the state in Poland: the legal position of Polish Muslims - Nalborczyk, Agata S. (Islam and Christian-Muslim relations, 2011)
Relations between the Polish state and Muslims living in its territory have a long history dating back to the fourteenth century, when a Muslim presence was first established in the area. The first Muslims to arrive in Poland were Tatars from the Golden Horde. Their influx continued for a few centuries and they were granted land in exchange for military service. The nature of mutual relations changed with time, along with changes in the structure of the state. Initially, there was a Polish-Lithuanian monarchy, but after 1795 the area inhabited by the Tatars fell under the rule of the Russian Empire. In 1918-1939, the reborn Polish state granted its inhabitants religious freedom and, even though Catholicism was privileged, Islam was officially recognized in 1936. The socialist state, in existence between 1944 and 1989, took an ideological stance against all religions. Since 1989, Poland has been a democratic state under the rule of law characterized by separation of state and religion. Thanks to the centuries-long presence of Tatars in Poland, Islam is an officially recognized denomination and the position of Muslims is much better than that of other religious minorities. This article details the historical development of relations between the Polish state and Muslims. The section on the twentieth century provides an analysis of relations between the state and religion and a description of Islam-related legislation in the Constitution and religious law, focusing on regulations concerning religious practices including marriage, dress code, ritual slaughter and religious instruction in school.